Exploring the Development of Bibliometric Research in Indonesia - Ratnasari, Wiwit; Amriza, Rona Nisa Sofia (UI Scholars Hub, 2026)
The growing availability of large bibliographic databases and analytical tools has accelerated the adoption of bibliometric methods across research fields worldwide. In Indonesia, bibliometric approaches have been widely applied across diverse domains; however, existing studies remain largely discipline-specific and lack a comprehensive national-level overview of how bibliometric research itself has developed. This study addresses this gap by conducting a systematic bibliometric analysis of bibliometric publications produced by Indonesian researchers. A total of 532 publications published between 2017 and 2025 were retrieved from the Scopus database and analyzed using bibliometric techniques, including descriptive analysis of study characteristics, co-authorship analysis, co-citation analysis, and keyword co-occurrence analysis with VOSviewer. The findings reveal that the development of bibliometric research in Indonesia has progressed through two phases: an initiation phase (2017–2020), characterized by relatively few but highly cited publications, and an expansion phase (2021–2026), marked by rapid growth and broader adoption across disciplines. These findings indicate that bibliometrics has evolved into a cross-disciplinary methodological bridge within the Indonesian research landscape, although its future development may depend on stronger integration between quantitative mapping techniques and theoretically grounded domain analysis.